Does Corporate Governance Matter for Bank Performance and Risk-taking? Insights from the Nepalese Banking Industry - Nepali, Som Raj (Finance & Economics Review, 2023)
Purpose: This study empirically examines the linkages of corporate governance with the performance and risk-taking of Nepalese banks. Methods: The study uses balanced panel data collected from annual reports [2010-2018] of the selected nineteen banks, including seven foreign-owned banks and twelve domestic banks. The study employs a descriptive and causal-comparative research design with the Ordinary Least Square (OLS) regression approach. Results: The results reveal that a greater number of board meetings and audit committee meetings leads to better performance and lower risk. The independent sample t-test results show that foreign-owned banks significantly differ from domestic banks using corporate governance mechanisms except for board size and audit committee size. Cohen's d results reveal that the number of board-level committees has a medium effect and all other corporate governance variables have a lesser effect on domestic banks than on foreign-owned banks. Implications: The study has policy-level implications for the regulators to emphasize the provisions relating to board size, audit committee size, and their respective meetings for enhancing financial stability. Similarly, the study findings also facilitate bankers to look after and make changes to corporate governance practices prudently. Originality: This study uses Tobin's Q to measure bank performance and employs a Z-score to measure bank risk-taking behavior, which makes it one of the very few studies that explain the impact of corporate governance on bank performance and bank risk-taking.